EULAR recommendations for calcium pyrophosphate deposition. Part II: Management. Issue 4 (20th January 2011) - Zhang, W; Doherty, M; Pascual, E; Barskova, V; Guerne, P-A; Jansen, T L; Leeb, B F; Perez-Ruiz, F; Pimentao, J; Punzi, L; Richette, P; Sivera, F; et al.
Abstract : Objectives: To develop evidence-based recommendations for management of calcium pyrophosphate deposition (CPPD). Methods: A multidisciplinary guideline development group of 15 experts, representing 10 European countries, generated key propositions for management of CPPD using a Delphi consensus approach. For each recommendation research evidence was searched systematically. Whenever possible, the effect size and number needed to treat for efficacy and RR or OR for side effects were calculated for individual treatment modalities. Strength of recommendation was assessed by the European League Against Rheumatism visual analogue scale. Results: Nine key recommendations were generated, including topics for general management, treatment of acute attacks, prophylaxis against recurrent acute attacks and management of chronic symptoms. It was recommended that optimal treatment requires both non-pharmacological and pharmacological treatments. For acute CPP crystal arthritis, cool packs, temporary rest and joint aspiration combined with steroid injection are often sufficient. For prophylaxis or chronic inflammatory arthritis with CPPD, oral non-steroidal anti-inflammatory drugs with gastroprotective treatment and/or low-dose colchicine 0.5–1.0 mg daily may be used. Other recommendations included parenteral or oral corticosteroid for acute CPP arthritis in those unresponsive or unsuited to other measures, and low-dose corticosteroid, methotrexate or hydroxychloroquine for chronic inflammatory arthritis with CPPD. Asymptomatic CPPD requires no treatment. Strength of recommendations varies from 79% to 95%. Conclusion: Nine key recommendations for management of CPP crystal associated arthritis were developed using both research evidence and expert consensus. Strength of recommendations was provided to assist the application of these recommendations.